Atividade comunitária e conscientização: uma investigação a partir dos modos de participação social - Vieira, Emanuel Meireles (2008)
This work is based on Góis’s verification that, among the many factors that act on the awereness process, the way to participate of communi¬tarian activity is one of them. It is asked from the statement of that the way to participate influences this process, defined here for Paulo Freire’s theory. It has as objective, therefore, discuss how the way to participate of communi¬tarian activity influences on the the awereness process. For in such a way, initially, it establishes a quarrel regarding the different forms to participate and the factors that act in the phenomenon of the participation. After that, from Communitarian Psychology, of the Liberating Education and the Historical-Cultural Theory of the Mind, it discourses concerning the psychic implications of the interactions human beings, arguing the concepts of: community, communitarian activity, conscience and awareness. A qualitative boarding was used, with ethnographic approach, interviewing a person who is part of Projeto de Educação em Células Cooperativas (PRECE), through the half-structuralized interview, with focus in the history of life of the interviewed one. Registers of the daily interview and of field, a total of seven visits had been become fullfilled. From now on, it was possible to analyze the way to participate of the citizen of the research and to carry through a thematic analysis of its interview. As result, we could verify that way of a more active and cooperative participation propitiates conditions so that the citizen in this way fortifies its interactions with the reality through the appropriation and significação of if relating, on the part of the individual.